Analisis Variabilitas Curah Hujan, Suhu Udara, Dan Suhu Permukaan Tanah Selama Periode 2000-2022 Di Pulau Bali Dengan Memanfaatkan Data Penginderaan Jauh - I Gede Agus Novanda; Wahyudin; Anak Agung Eka Andiani; Gusti Ayu Istri Pradnyandari Dewi (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Information regarding the characteristics and variability of climate in Bali Island remains relatively limited, despite its importance for supporting development planning, natural resource management, and disaster risk mitigation. This study aims to analyze the characteristics of rainfall, air temperature, and land surface temperature (LST) in Bali Island during the period 2000–2022 using remote sensing data. The datasets employed include CHIRPS for rainfall, ERA5-Land for air temperature, and MODIS MOD11A2 V6.1 for land surface temperature. Spatial and temporal analyses were conducted to identify climate patterns, variability, and the relationships among climate variables. The results show that the highest average rainfall occurred in January, reaching 318.38 mm/month, with an average of 19 rainy days per month, while rainfall intensity tended to be higher in May and October, corresponding to the transitional seasons. The average air temperature exhibited two annual peaks, occurring in April (24.77°C) and November (24.99°C), while the lowest temperature was recorded in August (23.38°C). Meanwhile, the highest average land surface temperature was observed in 2015 (28.7°C), whereas the lowest was recorded in 2022 (25.8°C). Spatially, the mountainous regions of central and northern Bali generally experienced higher rainfall and lower temperatures than other areas. The findings demonstrate that remote sensing data are effective for identifying regional climate characteristics and variability. The results are expected to provide valuable information for climate-based development planning, natural resource management, and climate change adaptation efforts in Bali Island.